Explaining Discrimination against Religious Minorities. Issue 2 (5th April 2017) - Finke, Roger; Martin, Robert R.; Fox, Jonathan
Abstract: Research has documented that religious minorities often face the brunt of religious discrimination. Yet formal tests, using global collections, have been lacking. Building on the religious economy theory and recent work in law and politics, we propose that minority religions face discrimination from the state because they represent unwanted competition for the state supported religion, are viewed as a threat to the state and larger culture, and lack support from an independent judiciary. Drawing on the recently collected Religion and State-Minorities collection on more than 500 minority religions, we find support for each of the propositions, though the level of support varies based on the targets of state discrimination. In general, the support is strongest when explaining discrimination against minority religion's institutions and clergy, but weakens when explaining more general discrimination against the membership.